Elucidation of prognostic factors in the acute phase of feline severe fever with thrombocytopenia syndrome virus infection - MATSUURA, Yukiko; HAMAKUBO, Emu; NISHIGUCHI, Akihiro; MOMOI, Yasuyuki; MATSUU, Aya (Journal of Veterinary Medical Science, 2024)
Severe fever with thrombocytopenia syndrome (SFTS) is a potentially fatal tick-borne zoonotic disease, endemic to Asian regions, including western Japan. Cats appear to suffer a particularly severe form of the disease; however, feline SFTS is not clinically well characterized. Accordingly, in this study, we investigated the associations of, demographic, hematological and biochemical, immunological, and virological parameters with clinical outcome (fatal cases vs. survivors) in SFTSV-positive cats. Viral genomic analysis was also performed. Viral load in blood, total bilirubin, creatine phosphokinase, serum amyloid A, interleukin-6, tumor necrotic factor-α, and virus-specific IgM and IgG differed significantly between survivors and fatal cases, and thus may have utility as prognosticators. Furthermore, survivor profiling revealed high-level of viremia with multiple parameters (white blood cells, platelet, total bilirubin, glucose, and serum amyloid A) beyond the reference range in the 7-day acute phase, and signs of clinical recovery in the post-acute phase (parameters returning to, or tending toward, the reference range). However, SFTSV was still detectable from some survived cats even 14 days after onset of disease, indicating the risk of infection posed by close-contact exposure may persist through the post-acute phase. This study provides useful information for prognostic assessments of acute feline SFTS, and may contribute to early treatment plans for cats with SFTS. Our findings also alert pet owners and animal health professionals to the need for prolonged vigilance against animal-to-human transmission when handling cats that have been diagnosed with SFTS.